2015
DOI: 10.1039/c4sm02456g
|View full text |Cite
|
Sign up to set email alerts
|

The effects of globotriaosylceramide tail saturation level on bilayer phases

Abstract: Globotriaosylceramide (Gb 3 ) is a glycosphingolipid present in the plasma membrane that is the natural receptor of the bacterial Shiga toxin. The unsaturation level of Gb 3 acyl chains has a drastic impact on lipid bilayer properties and phase behaviour, and on many Gb 3 -related cellular processes. For example:the Shiga toxin B subunit forms tubular invaginations in the presence of Gb 3 with an unsaturated acyl chain (U-Gb 3 ), while in the presence of Gb 3 with a saturated acyl chain (S-Gb 3 ) such invagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…They further speculated that unsaturated Gb3 species may be the essential ones for Gb3 concentrations [106], which would be in accordance to the described findings facilitating lipid compaction.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…They further speculated that unsaturated Gb3 species may be the essential ones for Gb3 concentrations [106], which would be in accordance to the described findings facilitating lipid compaction.…”
Section: Accepted Manuscriptsupporting
confidence: 61%
“…Description of the thermal Casimir force between membrane inclusions as presented in the literature and our calculations using the proximity force approximation of the thermal Casimir force between a pair of polygonal particles at separations that are small compared to their size, the dissipative particle dynamics simulations of nanoparticles adsorbed to a fluctuating membrane, showing that only when the nanoparticles suppress the membrane fluctuations do they experience a clustering force, reanalysis of trajectories from our previously published molecular dynamics (MD) simulations 14,18 showing that the binding of STxB to the membrane does not change the lipids’ chain order parameter nor their rotational diffusion, experimental protocol for adding the STxB toxin particles to the vesicles and cells, estimation of the membrane coverage due to STxB binding to Gb3 lipids, FCS experiments that are used to measure the decrease in diffusion as the toxin nanoparticles aggregate, and complete organic synthesis reactions for the PEG-modified Gb3 lipids (PDF)…”
mentioning
confidence: 99%
“…3, C and D) compared to Gb 3 -S. In general, formation of membrane invaginations occurs in three steps: 1) protein binding to the membrane, 2) line tension-driven formation of STxB-Gb 3 aggregates, and 3) generation of negative curvature leading to invaginations (protein cluster formation alone is not sufficient to induce membrane invaginations) (2). If saturated fatty acids are attached to Gb 3 , protein clusters are observed; however, invaginations in GUVs do not form, while unsaturated fatty acids facilitate membrane bending (1,20), which might be a result of the reduced lipid packing order (20). We found that subtle variations of the Gb 3 molecules such as chirality substantially changes protein/membrane organization, which in turn acts on the propensity of tubule formation in membranes.…”
mentioning
confidence: 96%